Dividend Payout Ratio and Factors Affecting Food and Beverage Companies on the IDX - Widyakto, Adhi; Prapti, Lulus; Triyani, Dian (Economics and Business Solutions Journal, 2022)
Effect of Debt to Equity Ratio on Dividend Payout Ratio Sourced in table 2, the t-statistic has a value of -2,641372 which is smaller than t-table 2 009, so that the t-statistic located in the Ha area is accepted. Not only that, it is supported by a probability value (p-value) of 0.0114 which is smaller than an alpha of 0.05. Thus, it can be concluded that the Debt to Equity Ratio (DER) affects the Dividend Payout Ratio (DPR) in the dining zone. and beverages listed on the IDX for the 2017-2020 period. This result is in line with Rindasari's previous research (2018). However, this result does not match the research conducted by Samrotun (2015) which states that the Debt to Equity Ratio has a positive effect on the dividend payout ratio. But it is different from the research conducted by Yurinawati and Andayani (2017) which shows that the Current Ratio does not affect the Dividend Payout Ratio.  Based on the results of the analysis and review, with illustrations of 10 food and beverage industries listed on the Indonesia Impact Exchange (IDX) in 2017-2020, as follows: Return on Assets, Current Ratio does not affect, but Debt to Equity Ratio, Firm Dimensions affect the dividend payout ratio.